Effect of AV3V lesion on the cardiovascular, fluid, and electrolytic changes induced by activation of the lateral preoptic area - Gonçalves, Patricia Constantino [UNESP]; Alves, Marcus Bravo [UNESP]; Silveira, JoséEduardo Nogueira [UNESP]; Saad, Wilson Abrão [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP]; Renzi, Antonio [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier, 1992)
In this study we investigated the effect of the anteroventral third ventricle (AV3V) lesion on the pressor, bradycardic, natriuretic, kaliuretic, and dipsogenic responses induced by the injection of the cholinergic agonist carbachol into the lateral preoptic area (LPOA) in rats. Male Holtzman rats with sham or electrolytic AV3V lesion were implanted with stainless steel cannula directly into the LPOA. Injection of carbachol (7.5 nmol) into the LPOA of sham rats induced natriuresis (405 ± 66 μEq/120 min), kaliuresis (234 ± 44 μEq/120 min), water intake (9.5 ± 1.7 ml/60 min), bradycardia (-47 ± 11 bpm), and increase in mean arterial pressure (28 ± 3 mmHg). Acute AV3V lesion (1-5 days) reduced the natriuresis (12 ± 4 μEq/120 min), kaliuresis (128 ± 27 μEq/120 min), water intake (1.7 ± 0.9 ml/60 min), and pressor responses (14 ± 4 mmHg) produced by carbachol into the LPOA. Tachycardia instead of bradycardia was also observed. Chronic (14-18 days) AV3V lesion reduced only the pressor response (10 ± 2 mmHg) induced by carbachol. These results showed that acute, but not chronic, AV3V lesion reduced the natriuretic, kaliuretic, and dipsogenic responses to carbachol injection into the LPOA. The pressor response was reduced in acute or chronic AV3V-lesioned rats. The results suggest that the lateral areas may control the fluid and electrolyte balance independently from the AV3V region in chronic AV3V-lesioned rats. © 1992.
Keywords: AV3V region; Cardiovascular control; Cholinergic system; Electrolyte balance; Fluid balance; Hypothalamus; Natriuresis; Thirst; carbachol; animal experiment; animal tissue; blood pressure; brain injury; brain third ventricle; controlled study; heart rate; intracerebral drug administration; male; natriuresis; nonhuman; priority journal; rat; thirst; Animal; Blood Pressure; Body Fluids; Carbachol; Cerebral Ventricles; Drinking Behavior; Electrolytes; Heart Rate; Hemodynamics; Injections; Male; Potassium; Preoptic Area; Rats; Support, Non-U.S. Gov't